Development of the “literary evolution” concept by Yuri Tynyanov in the works of Sergei Averintsev (ENTHYMEMA, 2022)
Since the concept of “literary evolution” proposed by Yuri Tynyanov could not be applied to the late Soviet official literature, Sergei Averintsev using this concept examined the relationship between philosophy, sophistry, rhetorics and everyday consciousness in classical Greece. Tynyanov's theory of “parallel series” turned out to be productive for the reconstruction of the tasks of the ancient philosopher and for the interpretation of Plato's dialogues. According Averintsev, Plato acted within the sophistic field, creating irreducible terminology and untranslatable phrases as a moment of the entire further evolution of Western literature. Consideration of Russian formalism as the context of Averintsev's thought proves his contribution to the discussion of Platonism as a tool for posing philosophical problems and of the perspective of philosophy in the postcolonial discussion.
Keywords: Russian formalism; Averintsev; Tynyanov; Plato; rhetorics